2015
DOI: 10.1186/s12864-015-1287-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the silk gland transcriptomes between the domestic and wild silkworms

Abstract: BackgroundBombyx mori was domesticated from the Chinese wild silkworm, Bombyx mandarina. Wild and domestic silkworms are good models in which to investigate genes related to silk protein synthesis that may be differentially expressed in silk glands, because their silk productions are very different. Here we used the mRNA deep sequencing (RNA-seq) approach to identify the differentially expressed genes (DEGs) in the transcriptomes of the median/posterior silk glands of two domestic and two wild silkworms.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 47 publications
5
90
0
Order By: Relevance
“…Total RNA from Cf-12- tomato leaves was extracted and analyzed, as previously described (Fang et al, 2015). The integrity of the isolated RNA was calculated, as previously described (Schroeder et al, 2006); and samples with an RNA integrity number >9.0 were used for libraries construction.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA from Cf-12- tomato leaves was extracted and analyzed, as previously described (Fang et al, 2015). The integrity of the isolated RNA was calculated, as previously described (Schroeder et al, 2006); and samples with an RNA integrity number >9.0 were used for libraries construction.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from three biological replicates for each treatment with three plants according to an RNeasy Plant Mini Kit extraction protocol and was then used in the RT-qPCR experiments (Schroeder et al, 2006; Fang et al, 2015). Total RNA was treated with DNase I, and oligo (dT) was used to isolate mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with its wild progenitor, B. mandarina , many phenotypic traits of the domestic silkworm have changed greatly, for example, silk yield, flight and body color. Indeed, silk yield of the domestic silkworm is about 3–5 times that of the wild silkworm (Normile, ; Takasu et al ., ; Fang et al ., ). However, little is known about the genetic mechanisms of increased silk yield in the domestic silkworm (Ma et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, little is known about the genetic mechanisms of increased silk yield in the domestic silkworm (Ma et al ., ). Our previous study suggested that the higher efficient biosynthesis and secretion of silk proteins may contribute to elevated silk yield in the domestic silkworm (Fang et al ., ). At present, most of the studies on silk yield focus on the protein‐coding genes and microRNAs (miRNAs) (Li et al ., ; Fang et al ., ).…”
Section: Introductionmentioning
confidence: 99%